Factors Associated With Renal Involvement in Primary Sjögren's Syndrome: A Meta-Analysis - Hong, Ruping; Xu, Dong; Hsieh, Evelyn; Xiang, Yirong; Zhao, Jiuliang; Wang, Qian; Tian, Xinping; Li, Mengtao; Zhao, Yan; Zeng, Xiaofeng (Frontiers in Medicine, 2020)
Background: Renal impairment is a critical complication in primary Sjögren's syndrome (pSS), resulting in chronic renal disease and even death. This meta-analysis was designed to find out the relevant factors of renal involvement in pSS. Methods: PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science were systemically searched until August 30, 2019. Studies were selected according to inclusion criteria, and data was extracted by two researchers independently. The Newcastle-Ottawa Scale was applied for quality assessment. Random- and fixed-effects models were used in this meta-analysis based on the result of the heterogeneity test. Meanwhile, a sensitivity analysis was conducted to investigate the cause of heterogeneity. Publication bias was shown in the funnel plot and evaluated further by Begg's and Egger's tests. Results: Of the 9,989 articles identified, five articles enrolling 1,867 pSS patients were included in the final analysis, 533 with and 1,334 without renal involvement. There was no statistical significance in age and gender between these two groups. According to the meta-analysis, anti-SSB antibody, and arthralgia showed a significant association with renal involvement in pSS, the overall odds ratio (OR) values of which were 1.51 (95% CI, 1.16–1.95) and 0.59 (95% CI, 0.46–0.74), respectively. On the other hand, the overall OR values of anti-SSA antibody, rheumatoid factor, dry eyes, and labial salivary gland biopsy were just 0.90 (95% CI, 0.49–1.64), 1.05 (95% CI, 0.59–1.86), 0.60 (95% CI, 0.34–1.06), and 1.38 (95% CI, 0.98–1.95), respectively. Conclusion: The presence of anti-SSB antibody is positively associated with renal involvement in pSS, while arthralgia is inversely associated. Large-scale prospective cohort studies are needed in the future to identify further risk factors.